Redefining the Role of School Principal in the Digital Era: Strategis for instilling Digital Ethics in Generation Alpha - Anas Fredika; Sunarto Sunarto; Ardhana Januar Mahardhani (FKIP - Universitas Riau, 2026)
The growing use of digital technology among Generation Alpha presents new challenges in shaping character and fostering digital ethics within educational settings. This study aims to examine the strategies and the redefined role of school principals in instilling digital ethics among students at MTsN 1 Madiun. Employing a descriptive qualitative approach with a single case study design, data were collected through interviews, observations, and documentation. Data analysis was conducted through the stages of reduction, presentation, and conclusion drawing using Miles and Huberman’s interactive model. The findings reveal that the principal plays a transformative role in shaping students’ digital ethics through three main strategies: integrating Islamic values into the school’s digital culture (cultural), establishing digital policies and regulations (structural), and strengthening teachers’ capacities through training and mentoring (instrumental). The study concludes that the success of cultivating digital ethics is determined by visionary, participatory, and contextual leadership. This research contributes to the enrichment of value-based leadership theory in the context of digital education and offers practical implications for formulating digital ethics policies in faith-based schools.